2005
DOI: 10.1292/jvms.67.543
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Feline Interferon-.ALPHA. Subtypes in Esherichia coli, and Their Antiviral Activity and Animal Species Specificity

Abstract: ABSTRACT. Two kinds of FeIFN-α consisting of 166 amino acids (aa) and 171 aa were expressed in Escherichia coli, and the purified proteins were tested for antiviral activity on homologous and heterologous animal cells. Crude FeIFN induced in feline cells revealed antiviral activity on both homologous and heterologous animal cells. In contrast, both types of recombinant FeIFN-α revealed antiviral activity only on the feline cells. All of the FeIFN-α subtypes showed high activity to vesicular stomatitis virus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…38 Feline interferon-omega (licensed for the treatment of canine parvovirus and feline leukaemia virus (FeLV] infections in some European countries) inhibits FCV replication in vitro; controlled field studies, however, are not available [EBM grade IV]. 39,40 In addition, no vaccine protects against all FCV field strains.…”
Section: Antiviral Therapymentioning
confidence: 99%
“…38 Feline interferon-omega (licensed for the treatment of canine parvovirus and feline leukaemia virus (FeLV] infections in some European countries) inhibits FCV replication in vitro; controlled field studies, however, are not available [EBM grade IV]. 39,40 In addition, no vaccine protects against all FCV field strains.…”
Section: Antiviral Therapymentioning
confidence: 99%
“…Although some broad-spectrum antivirals are effective against FCV in cell culture, they are too toxic for use in the cat [83]. Interferon is used by some, although to the authors' knowledge, published evidence for its effectiveness remains limited to in vitro studies [106], and it is not licensed for control of FCV-disease in Europe. Experimental trials of chimeric mouse-cat monoclonal antibodies have shown some promise in treatment [111,112].…”
Section: Treatmentmentioning
confidence: 99%
“…There are currently no direct acting antiviral drugs registered for the treatment of FCV, although the immune modulating drug recombinant feline interferon-v (rFeIFNv), which likely has indirect antiviral properties, has a registered indication for FCV treatment. Efficacy of both human and feline interferons has been demonstrated in vitro against FCV (Fulton and Burge, 1985;Mochizuki et al, 1994;Taira et al, 2005;Truyen et al, 2002) and the use of rFeIFN-v has been reported to have a positive therapeutic effect in FCV infected cats in experimental and field efficacy trials (Ninomiya et al, 1991;Ohe et al, 2008). Treatment with rFeIFN-v was also associated with an improvement in clinical signs in cats with refractory FCGS in a double-blinded placebo-controlled study, however FCV shedding was not monitored, making it unclear whether the improvement was due to the antiviral or immunomodulatory properties of interferon (Hennet et al, 2011).…”
Section: Introductionmentioning
confidence: 99%